THE SCALE OF MORAL CAPITAL: A RELIABILITY AND VALIDITY STUDY - Özgür Sami AKGÜL (Fırat University, 2020)
This study aims to develop a valid and reliable scale which can measure the moral capital of teachers. Firstly, a literature review has been made in order to develop the scale, and then an item pool with 66 items matching behaviours that moral teachers should have has been constituted. In accordance with the opinions received by experts, the items that are of similar nature, inarticulate, unclear and meaningless have been omitted from the scale and thus the 66-item scale has been reduced to 30 items. The research population of this study is, the teachers who work in public schools in Şehitkamil and Şahinbey districts of Gaziantep during 2018-2019 educational year. The teachers in the research sample have been determined by Simple Random Sampling, and in order to determine the construct validity of the scale, Exploratory Factor Analysis (EFA) has been applied to the data collected from 408 teachers in the research sample. Kaiser Meyer Olkin (KMO) value of the scale has been found as .805. It has been determined that Bartlett's Sphericity test finding (x2=746,739 p<.01) is meaningful and the variance obtained is % 60. According to EFA findings, the items whose item correlation value are under 0,30 have been omitted from the scale since their strengths to measure the item is weak. Afterwards, in order to examine the construct validity of the scale, Confirmatory Factor Analysis (CFA) has been applied to scale form consisting of 20 items. According to CFA findings, it has been determined that the factor load values of scale’s items vary from 0,32 to 0,66. The fit indices values of the scale’s items have been found as RMSEA: 0,074; SRMR: 0,067; GFI: 0,90; AGFI: 0,870; CFI: 0,910; NFI: 0,910; X2/df=3,17. The factor structure obtained from EFA findings, in terms of item statistics, has been found that it has been validated by CFA findings. Cronbach's Alpha, the internal consistency coefficient, which has been calculated for the whole scale has been found as .871. When look on dimension basis, all dimensions’ Cronbach’s Alpha values have been found above 70. When the values obtained at the end of the study are taken into consideration, it can be said that the moral capital scale is a valid and reliable scale consisting of 20 items and 5 dimensions.